Electronic Contracts and Their Legal Challenges: A Georgian Judicial Practice Perspective - Zaza Mtchedlishvili (European Scientific Journal, ESJ, 2026)
This article analyzes the "utopian" perceptions engendered by rapid technological advancement and the concomitant legal challenges arising in the real world. It examines key aspects of the digital economy, including electronic commerce, smart contracts, and their interplay with traditional legal norms, with a particular focus on Georgian legislation. Utilizing comparative-legal, analytical, and doctrinal methods, the research is grounded in contemporary civil law doctrines and the insights of renowned philosophers such as Berdyaev, Hayek, and Lessing. By analyzing judicial practice and legislation from the United States, Canada, Europe, and Georgia, the study provides a multidisciplinary assessment of the impact of technological progress.Particular attention is given to the formal requirements of transactions and the expression of intent in the digital realm. The study demonstrates that "utopian" promises such as boundless and seamless commercial spaces, often mask significant social and legal risks. The article establishes that despite their widespread adoption, "click-wrap" agreements lack a uniform doctrinal consensus regarding their compliance with classical standards of transaction authenticity, specifically concerning the conscious expression of intent and the identification of signatures.The research reveals that Georgian regulation of electronic transactions is limited and relies primarily on general norms, leading to inconsistent judicial practice. Specifically, an analysis of Supreme Court of Georgia decisions demonstrates that the absence of an electronic signature renders transactions involving immovable property void. The article concludes that the technological revolution necessitates a structural adaptation of legal systems to address emerging challenges effectively.It is recommended that Georgia incorporate European and German legal models, which view electronic signatures as essential for ensuring the authenticity of electronic transactions. This approach would enhance the security of digital communications and protect the interests of all parties, thereby minimizing the negative consequences of "utopian" technological progress and fostering a more equitable digital society.